Projeto experimental livro-reportagem “trilhando memórias - a era do trem em São Borja” - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This report talks about the experimental project carried out as Term Paper, about the time when rail services were active in the city of São Borja/RS. It was developed in the form of a printed report book, through interviews - throught the Oral History Technique - and exploratory historical research supported by bibliographic and documentary sources. The objective was to rescue the history of the railway, present in the city from 1913 until the end of the XX century, for the production and dissemination of the memory of this means of transportation that contributed to the development of the local economy, transported thousands of people and employed a lot of workers. The studies used in the production were the investigation about the history of the train in humanity, search of national, state, regional and local historical files, rescuing old journals and personal collections, inverviewing ex-railroaders, train riders, and politicians involved with the theme today. The book was structured according to a narrativeexplanatory logic, exposing the main events related to the railways' history, from the birth of the first locomotive, in Europe, to the end of the operations in São Borja, in a journalistic text with literary style touches. It concludes that the circulating trains in the city represented more that a mean of locomotion connected to the economic development and accessible to rural and city citizens: they were a space of a beneficial social and cultural dinamic, that remained in the memory and desire of a possible return.
Keywords: Ferrovias; Ferrovias - História; São Borja (RS); Viagens de trem; Railways; Railways - History; CNPQ::CIENCIAS SOCIAIS APLICADAS